UMPSA celebrates outstanding athletes in the 2024 Athlete Appreciation Ceremony - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 13 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised the 2024 UMPSA Athlete Appreciation Ceremony to celebrate the achievements and dedication of athletes who brought glory to the university throughout the past year.